Three-Year Experience of an Academic Medical Center Ombuds Office - Raymond, John R. (Acad Med, 2016)
An ombuds is an individual who informally helps people or groups (visitors) resolve disputes and/or interpersonal conflicts as an alternative to formal dispute resolution mechanisms within an organization. Ombuds are nearly ubiquitous in many governmental, business, and educational settings but only recently have gained visibility at medical schools. Medical schools in the United States are increasingly establishing ombuds offices as part of comprehensive conflict management systems to address concerns of faculty, staff, students, and others. As of 2015, more than 35 medical schools in the United States have active ombuds Web pages. Despite the growing number of medical schools with ombuds offices, the literature on medical school ombuds offices is scant. In this article, the authors review the first three years of experience of the ombuds office at the Medical College of Wisconsin, a freestanding medical and graduate school with a large physician practice. The article is written from the perspective of the inaugural ombuds and the president who initiated the office. The authors discuss the rationale for, costs of, potential advantages of, and initial reactions of faculty, staff, and administration to having an ombuds office in an academic medical center. Important questions relevant to medical schools that are considering an ombuds office are discussed. The authors conclude that an ombuds office can be a useful complement to traditional approaches for conflict management, regulatory compliance, and identification of systemic issues.